2016
DOI: 10.1111/age.12483
|View full text |Cite
|
Sign up to set email alerts
|

Novel Y‐chromosome short tandem repeats in Sus scrofa and their variation in European wild boar and domestic pig populations

Abstract: SummaryY-chromosome markers are important tools for studying male-specific gene flow within and between populations, hybridization patterns and kinship. However, their use in non-human mammals is often hampered by the lack of Y-specific polymorphic markers. We identified new male-specific short tandem repeats (STRs) in Sus scrofa using the available genome sequence. We selected four polymorphic loci (5-10 alleles per locus), falling in one duplicated and two single-copy regions. A total of 32 haplotypes were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The gross haplotype diversity of swamp buffalo was 0.308 ± 0.026. This value is close to that of domestic sheep (0 ~ 03849; Zhang et al, 2014), but lower than that of cattle (0.422 ± 0.3; Edwards et al, 2011) and pig (0.491 ± 0.077-0.711 ± 0.118; Iacolina et al, 2016). Our results suggest a low level of Y-chromosome genetic diversity in swamp buffalo.…”
Section: Discussionsupporting
confidence: 63%
“…The gross haplotype diversity of swamp buffalo was 0.308 ± 0.026. This value is close to that of domestic sheep (0 ~ 03849; Zhang et al, 2014), but lower than that of cattle (0.422 ± 0.3; Edwards et al, 2011) and pig (0.491 ± 0.077-0.711 ± 0.118; Iacolina et al, 2016). Our results suggest a low level of Y-chromosome genetic diversity in swamp buffalo.…”
Section: Discussionsupporting
confidence: 63%
“…Throughout its history, the wild boar has been strongly influenced by human practices such as hunting, pig domestication, and animal translocation (Larson et al, 2005;Scandura, Iacolina, & Apollonio, 2011). Previous studies revealed the complex genetic structure of wild boar populations in Eurasia, including multiple domestication events and gene flow between wild boar and domestic pig breeds (Iacolina et al, 2016;Larson et al, 2005;Ramíres et al, 2009;Ribani et al, 2019;Šprem et al, 2014). Previous studies revealed the complex genetic structure of wild boar populations in Eurasia, including multiple domestication events and gene flow between wild boar and domestic pig breeds (Iacolina et al, 2016;Larson et al, 2005;Ramíres et al, 2009;Ribani et al, 2019;Šprem et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, analysis of the changes in the geographical range of S. scrofa could aid our understanding of not only the global patterns of evolution and ecosystem change (Anijalg et al, 2018). Previous studies revealed the complex genetic structure of wild boar populations in Eurasia, including multiple domestication events and gene flow between wild boar and domestic pig breeds (Iacolina et al, 2016;Larson et al, 2005;Ramíres et al, 2009;Ribani et al, 2019;Šprem et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The use of molecular genetic methods makes it possible to characterize animal populations and determine the degree of their genetic differentiation. Various types of DNA markers are used to characterize the wild boar populations from Russia: mitochondrial DNA [ 10 , 11 , 12 ], Y-chromosome [ 12 , 13 ], STR [ 14 , 15 , 16 , 17 ], SNP [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%